New ways to leadership development: A picture paints a thousand words. Issue 1 (February 2013) - Schyns, Birgit; Tymon, Alex; Kiefer, Tina; Kerschreiter, Rudolf
Mainstream leadership development often focuses only on leaders themselves and existing models that purport to help these individuals become better at leading. However, this sort of leader development (as opposed to leadership development) is questionable with regard to efficiency and effectiveness. We argue here that this may be due to a lack of acknowledgement of leaders' (and followers') implicit leadership theories (Eden and Leviatan, 1975) in the context of leader and leadership development. In an attempt to broaden the scope of leadership development, we present the results of using a drawing exercise as a learning tool. This exercise serves to assess leaders' (and followers') implicitly held images of leaders and allows for contextual information derived from the exercise to be included in development interventions. Results show that participants draw metaphors and symbols as well as real and generic people. Furthermore, most drawings are of male leaders, and only few drawings contain followers. Based on the results, we critically reflect upon implications for leadership learning and development and argue that implicit leadership theories can provide a valuable starting point for leadership development.